Formalization of operational management and its impact on the innovativeness of IT companies from Lubuskie Voivodeship - Inków, Monika (Zielona Góra: Faculty of Economics and Management Press)
In the changing environment, innovation gives organizations a chance to survive and develop. Researchers indicate that successfully implemented innovations are a source of competitive advantage for an organization. In source literature we can find examples of various tools recommended by the authors that increase the probability of innovation success.
Keywords: IT industry; formalization; innovation; branża IT; formalizacja; innowacyjność